Lean Office in Administrative Billing and Vendor Payment Processes: A Systematic Literature Review - Islamicsia, Princeca DW; Karningsih, Putu Dana (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2026)
Administrative billing and vendor payment processes frequently experience delays due to document waiting times, repeated verification, and fragmented information flows. Although Lean Office has been widely adopted to reduce non-value-added activities in office environments, evidence regarding its implementation remains fragmented, particularly in billing and vendor payment processes. This study systematically reviews Lean Office implementation in administrative activities, focusing on billing, document verification, approval flows, and vendor payments. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, literature was collected from Scopus and Google Scholar using keywords related to Lean Office, administrative waste, billing, vendor payments, document verification, and non-value-added activities. From 59 initial records, eight articles met the inclusion and quality criteria and were analyzed using thematic synthesis. The findings reveal that waiting, extra processing, defective information, and document transportation are the most common forms of waste. Value Stream Mapping, Process Activity Mapping, root cause analysis, and standardization are the predominant analytical approaches. The review links major waste categories with practical improvement strategies, including document standardization, simplified approval procedures, digital integration, service-level targets, and early document validation. These findings provide practical guidance for redesigning billing and vendor payment processes to improve administrative efficiency, transparency,  process reliability.